Validity, Reliability, and Confirmatory factor structure of the Persian version of Emotion and Motivation Self-Regulation Questionnaire (EMSR-Q) - Norouzi, Hossein; Hasani, Jafar; Shah hosseini, Meysam (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: Emotion and Motivation Self-regulation plays an important role on student learning at classroom, so presence of appropriate tools for evaluating and assessing this structure is necessary. The aim of this study was to investigate the validity, reliability and confirmatory factor structure of the Persian version of Emotion and Motivation Self-Regulation Questionnaire (EMSR -Q). Methods: The present study had a descriptive and Psychometric design, and the statistical population included all middle and high school students of Semnan city. After providing double translation technique, Persian version of EMSR -Q carried out within 306 students from ages 12 to 16 years old. The study sample selected through random sampling method. Internal consistency and Item rest correlations methods were used to investigate the scale validity and the reliability were investigated by confirmatory factor analysis, subscales correlations, and criterion validity. Data were analyzed using SPSSV19 and LISRELV8.80 softwares. Results: Chronbach’s alpha coefficients range (0/71 to 0.86) implied appropriate Internal consistency of this scale and its subscales. Results of confirmatory factor analysis supported five factor structures (Avoidance oriented Self Regulation, Performance oriented Self Regulation, Negative Self Regulation of Stress, Positive Self Regulation of motivation, and Process Oriented Self Regulation) of scale. There were Average and meaningful correlation coefficients between the scales of Persian version of EMSR -Q with Cognitive Emotion Regulation and Educational Motivation Questionnaires. In addition, the correlation coefficients between subscales were high. Conclusion: It can be concluded that Persian version of EMSR -Q has a good validity and reliability in Iranian population and can be practical in different fields.